Residents' perspective on duty hours at an Israeli tertiary hospital - Elad Apt; Tslil Regev; Jacob Shapira; Ori Haberfeld; Ori Samuel Duek; Ronen Bar-Yoseph (BMC, 2022)
Abstract Background Specialization in medical professions is considered a challenging and intensive period due to the number and sequence of duty hours. Considering the effect of duty hours on residents, both physically and mentally, several models have been created over the years to address this complexity. The two main model schools aim to decrease the duty hour length and night shift (i.e., night float, NF) frequency. In recent years, duty hours have become a source of disagreement and frustration among the medical community, both residents and attendings. A possible change in the duty hour structure may affect residents in terms of several parameters, such as patient safety, the well-being of the physician and the degree of training of the resident. Purpose (1) To investigate medical residents' perspectives on their duty hours utilizing online questionnaires on their effect on the work environment and (2) to assess residents' preferences in relation to the suggested shortened shift and NF models. Methods Questionnaires were emailed to all residents (main residents and fellows) at an Israeli tertiary medical center between March 2020 and April 2020. Questions were scored from 1 (disagree) to 5 (fully agree). Results Two hundred and sixty residents (227 main residents, 43 fellows) participated in the study (40% female). The score for the degree of balance between work and personal life was low (0.9±1.99). The shortened shift model was perceived by the residents as more compatible with a balanced lifestyle than the NF model (3.77 ± 1.20 and 3.14 ± 1.26, respectively, P < 0.0001). Neither model was considered to risk impairing professional training (2.33 ± 1.45 and 2.47 ± 1.25, respectively, P = 0.12). Overall, 74% of the residents were not willing to lower their income if the decision were made to change models, and 56% were not willing to increase the number of shifts. Conclusions There is agreement among residents that shortening shift hours to 16 h would have a positive effect on the balance between personal life and work. In the eyes of residents, the change would not impair their training during residency.